(untitled) (Dama Academic Scholarly Journal of Researchers, 2025)
The study aimed to examine the efficiency of Human Resource Planning (HRP) and its impact on the Information Services Department (ISD). The study, which contains the research design, research population, sample, sampling procedure and data gathering instruments. It also sought to determine whether there are HRP policies and practices in the ISD; to establish whether the Human Resource Planning practices and procedures within the ISD are functioning effectively; and to identify the challenges associated with providing a framework to guide the implementation of HRP in the ISD. The results of the study reveal that most of the ISD staff lack in-depth knowledge of Human Resource Planning, and therefore, it is not well practised by senior officers. The study concludes that the organisation is proactive in recruiting and retaining employees. A recommendation for the Information Services Department towards an effective Human Resource Planning for the organisation